A universally applicable definition for domestication - Kathryn A. Lord; Greger Larson; Robin G. Allaby; Elinor K. Karlsson (Proceedings of the National Academy of Sciences, 2025)
The process of domestication is commonly perceived as a human achievement, and domestic species are typically assumed to be those under human control. Domestic species have emerged from a greater diversity of interactions than this perspective allows, and none of the many definitions proposed for domestication can readily, reliably, and consistently distinguish domestic and nondomestic populations. Here, we propose that the process of domestication should instead be defined solely as evolution of a nonhuman population in response to an anthropogenic niche and that a domestic population is one that cannot sustain itself outside of an anthropogenic niche. As a result, this definition does not require comparisons with a presumed and largely unobservable ancestor. Instead, it focuses on the observable relationship between a nonhuman population and humans. It also avoids making assumptions about how domestication happens, thus enabling an exploration of the mechanisms underlying the process of adaptation to an anthropogenic niche. By applying this definition to plants, animals, and microbes, we illustrate its utility for investigating the evolution of the relationship between humans and other species and for anticipating which species are likely to survive in an increasingly human-influenced world. Domestication is simply an evolutionary process resulting from the interaction between two species, one of which is human. As we work to protect Earth’s biodiversity, this definition allows us to understand why, in response to the conditions human societies create, some species survive and thrive, while others struggle and go extinct.